Protocol: Weight-adjusted effective volume of 0.5% ropivacaine for combined costoclavicular brachial plexus block–cervical plexus blocks undergoing arthroscopic shoulder surgery: A dose-finding study protocol - Jianlin Wang; Liyong Yuan; Zhong Mei; Zhimin Sheng; Xiaolu Huang; Miao Zhu (PLoS ONE, 2025)
Introduction Rotator cuff injuries are common clinically, and arthroscopic repair is widely applied. Postoperative analgesia can be assisted by the interscalene brachial plexus block; however, it comes with side effects, among which a high incidence of hemidiaphragmatic paralysis (HDP) is included. Costoclavicular brachial plexus–cervical plexus blocks (CCB–CPBs) offer comparable analgesia with lower HDP risk, yet local anesthetic volume issues can affect outcomes. In patients undergoing arthroscopic shoulder surgeries under general anesthesia with CCB–CPBs, the aim is to determine the optimal dose of ropivacaine for postoperative analgesia while avoiding hemidiaphragmatic paralysis (HDP), Methods and analysis This trial will be a prospective, single-arm, double-blind dose finding study. We plan to enroll 40 patients who will be scheduled to undergo arthroscopic shoulder surgeries under anesthesia that combines general anesthesia with CCB–CPBs. The volume of the local anesthetic will be determined by adopting the Up-and-Down sequential allocation study design. The primary outcome will be the numerical rating scale (NRS) scores of the patients prior to their departure from the post-anesthesia care unit (PACU). As for the secondary outcomes, they will include the ipsilateral diaphragmatic excursion, the characteristics of the sensory–motor block, the occurrence of complications, as well as the consumption of fentanyl during the operation. Ethics and dissemination Approval for the protocol of this study was granted by the Ethics Committee of Ningbo No. 6 Hospital in Zhejiang Province, China, on July 29, 2024 (Approval No. 2024-67L). Once the study is completed, we are committed to guaranteeing that the results will be accessible to the public, irrespective of the outcome. This will involve either publishing them in an appropriate journal or presenting them orally at academic conferences. Trial registration Trial registration number ChiCTR2400090292